(untitled) (Eurasian Research Bulletin, 2022)
The article discusses some features of the English language of law due to the influence of Roman and Norman legal culture, which cause certain difficulties in its study and translation of legal texts. Special attention is paid to the ambiguity of legal terms of the English language, Latin and French borrowings, legal realities.